Performance Evaluation Using the Malcolm Baldrige Criteria for Performance Excellence in the AVP Production Department of PT. XYZ - Nikita Dinda Purnamasari; Iriani Iriani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the era of intense global competition, companies must ensure that all organizational elements function optimally and align with strategic goals. PT. XYZ, a seafood processing company under X Group, faces challenges in achieving production targets, with an average realization of 59% in the first half of 2024. High employee turnover (13%) and dissatisfaction with wages and working conditions have been identified as key issues impacting performance. These challenges underscore the need for a comprehensive evaluation to improve productivity and achieve performance excellence. This study aims to evaluate the performance of the AVP production department at PT. XYZ using the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE). Data collection involved distributing questionnaires to 30 respondents, including managers, supervisors, Rnd, Purchasing, and employees, followed by validity and reliability testing using Smart PLS software. The evaluation results indicate that the AVP production department achieved a total score of 814.53, placing it in the "Benchmark Leader" category. This score reflects strong performance across the seven MBCfPE criteria, demonstrating effective leadership, strategic planning, and operational focus. However, areas such as workforce engagement and satisfaction require further improvement. These findings provide actionable insights to enhance employee retention, operational efficiency, and overall performance. The results affirm that PT. XYZ's AVP production department has established itself as a leader in the seafood processing industry, offering a model for excellence that can inspire similar organizations.